Aiming for evidence-based best practices in thoracic surgery—leadership in surgery - Villeneuve, Patrick James; Gilbert, Sebastien (Journal of Thoracic Disease; Vol 10, Supplement 32 (November 20, 2018): Journal of Thoracic Disease (Enhanced Recovery: The Evidence Supporting Best Perioperative Care in Thoracic Surgery), 2018)
Lung cancer remains a compelling cancer problem worldwide—according to data from the International Agency for Research on Cancer, over 2 million new cases of lung cancer will be diagnosed worldwide in 2018. More sobering are the 1.7 million deaths anticipated this year as a result of lung cancer.